Efektivitas Kacamata Pb pada Pemeriksaan Gigi Menggunakan Pesawat Dental Panoramic Berdasarkan Laju Dosis Radiasi - Latifah Aulia Rasyada; Dian Milvita; Nunung Nuraeni (Universitas Andalas, 2023)
The eyes is one of the sensitive organs that can be damaged if exposed to radiation. Pb glasses are one of the radiation protection tools. The use of Pb glasses in minimal dental X-ray examinations will cause cataracts in the patient's eyes, so research has been conducted on the effectiveness of Pb glasses in dental examinations using dental panoramic plane based on radiation dose rates.Â The study aims to determine the radiation dose received after and before passing through Pb glasses, determine the effectiveness of Pb glasses during dental X-ray examinations, and evaluate the effect of using Pb glasses on patient image results. Data were collected using three Pb glasses on a dental panoramic plane irradiation. Pb glasses are fitted to patients with thin, normal and overweight categories, this is because patients have different facial shapes and sizes. Determination of radiation dose value and effectiveness was done by attaching TLD-100 to the outside and inside of the Pb glasses lens. The effect of using Pb glasses was evaluated with a radiology specialist through interviews. The results obtained were that there was no radiation dose received by the eyes after passing through Pb glasses, the effectiveness of all Pb glasses was 100%, and the use of Pb glasses did not affect the results of dental X-ray images during examinations using dental panoramic plane.